Recent Advances in Non-Precious Metal Single-Atom Electrocatalysts for Oxygen Reduction Reaction in Low-Temperature Polymer-Electrolyte Fuel Cells - Zagal-Moya, J; Zagal-Moya, J (John Wiley and Sons Inc, 2023)
Fuel cells have emerged as a promising clean electrochemical energy technology with a great potential in various sectors, including transportation and power generation. However, the high cost and scarcity of the noble metals currently used to synthesise electrocatalysts for low-temperature fuel cells has hindered their widespread commercialisation. In recent decades, the development of non-precious metal electrocatalysts for the cathodic oxygen reduction reaction (ORR) have gained significant attention. Among those, electrocatalysts with atomically dispersed active sites, referred to as single-atom catalysts (SACs), are gaining more interest. Nanocarbon materials containing single transition metal atoms coordinated to nitrogen atoms are active electrocatalysts for the ORR in both acidic and alkaline conditions and thus have a great promise to be utilised as non-precious metal cathode electrocatalysts in low-temperature fuel cells. This review article provides an overview of the recent advancements in the utilisation of transition metal-based SACs in proton exchange membrane fuel cells (PEMFCs) and anion exchange membrane fuel cells (AEMFCs). We highlight the main strategies and synthetic approaches for tailoring the properties of SACs to enhance their ORR activity and durability. Based on the already achieved results, it is evident that SACs indeed could be suitable for the cathode of the low-temperature fuel cells. © 2023 Wiley-VCH GmbH.